Analysis of Socio-Economic Conditions of Working Women and the Role of Built Environmentto Enhance Quality of Lifein Islamabad (Journal of Asian Development Studies, 2024)
This research study was conducted to study the socio-economic conditions of the working women who work in the industrial sector in Islamabad and its surroundings, along with the impacts of the built environment on improving their quality of life indoors.For evaluation of the research problem, the ten factories in the Industrial area of Islamabad were selected as a population. Out of them, 150 women workers were selected as a sample for this study. For data collection, questionnaires and interview schedules were used, and after collection, the raw data was analyzed, constructed in tabulated form and narrated for better understanding. The study demonstrates that 46.0% of respondents had 35 to 50 years of age recorded with 55.33% matric education level, 68.67%of they reported married group and 50.6%of them had up to 5 years of job experience with designation55.33% of women workers recorded with supporting group (class four) which is followed by clerical (38.67%) and officer (6.0%). The data on the relation between machines and social life showed that machines had both kinds of impacts on women workers in industries. In some places, they think that they do not do not utilize their strengths. It was also concluded that the built indoor spaces and aspects of privacy in the work environment play a vital role in enhancing the spaces for privacy and enabling higher user satisfaction in the case of women in the workforce through the architectural design of these spaces